Endless recrystallization of high-entropy alloys at high temperature. (20th November 2022) - Wu, Qingfeng; Wang, Zhijun; He, Feng; Yang, Zhongsheng; Li, Junjie; Wang, Jincheng
Highlights: Endless recrystallization behaviors at high temperature (∼0.6Tm) were found for the first time in an FCC-based high-entropy alloy. Recrystallization volume fraction maintained stable at ∼50% and recrystallized grains were stable at ∼1 μm even after annealing at 700 °C for 1440 h. Stabilization mechanisms of the heterostructures were attributed to the competitive behaviors among recovery, recrystallization, grain growth, and precipitation. The heterostructured alloy exhibited excellent mechanical properties of ∼1.6 GPa tensile strength at room temperature and ∼1.1 GPa tensile strength at 600°C even after exposure at 700 °C for 720 h. Abstract: In traditional physical metallurgy, once recrystallization occurs, it will proceed to 100% along with time even at relatively low temperatures, resulting in the limited thermal stability of partially recrystallized alloys. Here, we proposed the strategy of achieving the endless recrystallization state at high temperature (∼0.6 T m ) in high entropy alloys for the first time. The partially recrystallized microstructures remained stable after annealing at 700 °C for 1440 h toward endless recrystallization with kinetics analysis. Benefiting from the ultra-thermostable heterostructures, the alloy exhibited excellent mechanical properties of ∼1.6 GPa tensile strength at room temperature and ∼1.1 GPa tensile strength at 600 °C even after exposure at 700 °C for 720 h. The kinetics of recovery, recrystallization, grain growth, and precipitate coarsening were quantitatively analyzed to uncover the mechanisms of endless recrystallization. The results revealed that the stable state of 50% recrystallization at 700 °C can be attributed to the precipitates inhibited recrystallization and the continued recovery decreased stored energy in the non-recrystallized regions. Furthermore, the grain size was stable in the recrystallized regions due to the strong pinning effect of the intergranular precipitates with slow coarsening rates. These findings created a brand-new state of endless recrystallization with the combination of recovery and recrystallization, which can significantly broaden the service temperature range of heterogeneous materials. Graphical abstract: Image, graphical abstract